Characterization of GFRα‐1‐Positive and GFRα‐1‐Negative Spermatogonia in Neonatal Pig Testis. Issue 6 (28th June 2013) - Lee, KH; Lee, WY; Kim, JH; Yoon, MJ; Kim, NH; Kim, JH; Uhm, SJ; Kim, DH; Chung, HJ; Song, H
Contents: Type A spermatogonia, including spermatogonial stem cells, are primary cells that maintain spermatogenesis and produce spermatozoa. Many spermatogonial markers have been reported in rodents. However, few markers have been identified in pig spermatogonia. Despite the lack of information, it is necessary to separate pure spermatogonial cells from whole testicular cells to understand the mechanism of spermatogenic meiosis and to establish spermatogonial stem cells for further biotechnological studies. The purpose of this study was to identify glial cell–derived neurotrophic factor receptor alpha‐1 (GFRα‐1) as a surface marker for early spermatogonia in neonatal pig testes. Histological analysis of 3‐day‐old pig testes revealed that type A spermatogonia, which lack heterochromatin, could be distinguished in neonatal pig testes. Immunohistochemistry of neonatal pig testes with GFRα‐1 antibody identified that some of the spermatogonial cells expressed GFRα‐1 on the cell membrane. Co‐immunostaining with both GFRα‐1 and protein gene product 9.5 (PGP 9.5) detected PGP 9.5 in all spermatogonia of neonatal pig testes, whereas GFRα‐1 was not detected on the surface of some PGP 9.5‐positive cells, indicating that some of the spermatogonial cells were PGP 9.5 positive and GFRα‐1 negative. After immunomagnetic cell sorting using a GFRα‐1 antibody, both GFRα‐1‐positive and GFRα‐1‐negative cells expressed PGP 9.5. Identifying the differential mRNA expression of both GFRα‐1‐positive and GFRα‐1‐negative cells using reverse transcription–polymerase chain reaction analysis revealed the expression of promyelocytic leukaemia zinc finger, octamer‐binding protein 4 and homeobox transcription factor in both cell types. These results suggest that GFRα‐1‐positive and GFRα‐1‐negative spermatogonia exist in PGP 9.5‐positive spermatogonia during the early stage of pig testes spermatogenesis, and that GFRα‐1 can be used for sorting PGP 9.5‐expressing spermatogonia.